2007
DOI: 10.1021/om7004222
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotrimerization Reactions Catalyzed by Rhodium(I) Half-Sandwich Complexes:  A Mechanistic Density Functional Study

Abstract: We propose and examine a comprehensive mechanism of the [(η 5 -C 5 H 5 )Rh]-catalyzed [2+2+2] cycloadditions of acetylene to benzene and of acetylene and acetonitrile to 2-methylpyridine, based on an extensive and detailed exploration of the potential energy surfaces using density functional theory. Both processes involve the formation of a coordinatively unsaturated 16-electron metallacycle, occurring after the replacement of the ancillary ligands L of the catalyst precursor of general formula [(η 5 -C 5 H 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
110
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(126 citation statements)
references
References 62 publications
16
110
0
Order By: Relevance
“…[14,15,17] On the other hand, similar barriers but lower exothermicities were reported for RhCp and CoCp-catalysed cyclotrimerisations. [10,17,18] As found previously in similar Co and Rh complexes, the 15-A3 complex exhibits p localisation with C a À C b and C b À C b bond lengths of 1.351 and 1.453 , respectively, despite the presence of metal lone pairs that could favour the formation of an aromatic ring. [10,18] The RhÀ C bond length of 2.04 is not far from the average crystallographic bond length of 2.01 .…”
supporting
confidence: 70%
See 3 more Smart Citations
“…[14,15,17] On the other hand, similar barriers but lower exothermicities were reported for RhCp and CoCp-catalysed cyclotrimerisations. [10,17,18] As found previously in similar Co and Rh complexes, the 15-A3 complex exhibits p localisation with C a À C b and C b À C b bond lengths of 1.351 and 1.453 , respectively, despite the presence of metal lone pairs that could favour the formation of an aromatic ring. [10,18] The RhÀ C bond length of 2.04 is not far from the average crystallographic bond length of 2.01 .…”
supporting
confidence: 70%
“…The reaction mechanism for the alkyne cyclotrimerisation reaction catalysed by [CoCp(L) 2 ] (Cp= cyclopentadiene; L = CO, PR 3 , THF and olefin), [10][11][12][13] [RuCpCl] [14][15][16][17] complexes and the {RhCp} [18] and {RhInd} (Ind = indene) [18] fragments has been analysed in these DFT studies. The generally accepted reaction mechanism is drawn in Scheme 3.…”
Section: Various [2+2+2] Cyclotrimerisation Processes Catalysed By Thmentioning
confidence: 99%
See 2 more Smart Citations
“…[14] A previous study found that solvent effects due to toluene and acetonitrile in [2+2+2] cycloadditions are minor, likely due to the absence of charged or polarised intermediates and transition states in the reaction mechanism. [28] Because the reactions studied were carried out in toluene, solvent effects have not been included in the present calculations. Finally, because there are no experimental data suggesting the presence of paramagnetic intermediates, our studies were limited to the singlet potential energy surfaces.…”
Section: Methodsmentioning
confidence: 99%